1992
DOI: 10.1136/ard.51.9.1069
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of the dorsal and lumbar spine in osteoporosis.

Abstract: The presence of normal bone density values in the lumbar spine is often assumed to exclude osteoporosis. Eleven cases are reported in which normal lumbar spine bone density and radiology were associated with one or more dorsal spine fractures; the diagnosis was postmenopausal osteoporosis in eight patients and corticosteroid induced osteoporosis in three. These findings suggest that spinal osteoporosis may sometimes be a focal disorder and emphasise the need for dorsal spine radiology in addition to bone densi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…The mechanical stresses acting on the thoracic spine are very different from those affecting the lumbar spine and may predispose to thoracic spine disease in some individuals. The results of this study confirm previous observations in selected patients with osteoporosis [7] and demonstrate that these also apply to populationbased women. Similarly, Bernecker et al [30] recently reported that bone density in the lumbar spine did not show any correlation with the spinal deformity index, based on radiological assessment of the spine from T4 to L5, in women with post-menopausal osteoporosis.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The mechanical stresses acting on the thoracic spine are very different from those affecting the lumbar spine and may predispose to thoracic spine disease in some individuals. The results of this study confirm previous observations in selected patients with osteoporosis [7] and demonstrate that these also apply to populationbased women. Similarly, Bernecker et al [30] recently reported that bone density in the lumbar spine did not show any correlation with the spinal deformity index, based on radiological assessment of the spine from T4 to L5, in women with post-menopausal osteoporosis.…”
Section: Discussionsupporting
confidence: 91%
“…In recent years, accurate and produce artefactually high BMD, normal lumbar spine precise assessment of bone mass at potential fracture BMD is generally interpreted as excluding spinal osteosites has become possible with techniques such as dual porosis. In a retrospective survey of 300 patients referred energy X-ray absorptiometry (DEXA), single photon for bone densitometry, we recently reported the presence absorptiometry and quantitative computed tomography, of one or more vertebral deformities in the thoracic spine Prospective studies have demonstrated an increasing in 11 patients with a normal lumbar spine assessed gradient of fracture risk with decreasing bone mineral by both bone densitometry and radiology, indicating density (BMD), a reduction of one standard deviation differential bone loss in the lumbar and thoracic spine in BMD being associated with a two to three-fold [7]. In this prospective study we have investigated the increase in fracture risk [2][3][4][5].…”
mentioning
confidence: 98%
“…Secondly, measurement of bone mineral density in the spine may be affected by the presence of extraskeletal calcification, osteophytes, scoliosis, and vertebral deformity, particularly in elderly subjects 16. Thirdly, the distribution of osteoporosis within the spine may be heterogeneous, with differential involvement of the dorsal spine17; lateral radiographs of the dorsal spine should therefore be performed in addition to bone densitometry in patients who complain of loss of height or pain in the dorsal spine or who have evidence of dorsal kyphosis. Finally, osteomalacia also results in low bone mineral density measured by absorptiometric techniques and should be excluded in patients at increased risk of vitamin D deficiency and osteomalacia.…”
Section: Measurement Of Bone Massmentioning
confidence: 99%
“…However, the prevalence of VFs is not equally distributed across the spine [ 4 ], and in the thoracic spine, it is highest at T7–T8 and T11–T12 [ 5 7 ]. The reasons for this bimodal distribution of VFs remain unclear.…”
Section: Introductionmentioning
confidence: 99%